A BIOPSYCHOSOCIAL APPROACH TO UNDERSTANDING THE INTERRELATIONSHIPS AMONG SEXUAL BEHAVIOUR, AGGRESSION, SOCIAL STATUS, AND HORMONES - Sunderani, Shafik A. (My University, 2012)
Sex differences, hormones and intrasexual competition and their relation to social status and romantic partner attraction were examined, uniting two bodies of literature: status-striving and romantic attraction. In Chapter 2 different forms of social status, (i.e., dominance, power, popularity, prestige) were examined as they relate to testosterone levels in men and women. Factor analysis revealed that dominance was a separate psychological construct from power, popularity and prestige. Furthermore, a positive association was shown between dominance and testosterone levels whereas lower testosterone levels were associated with the power, popularity and prestige composite. In Chapter 3 psychopathy and indirect aggression were examined in relation to cortisol levels, again in men and women. Results indicated that lower cortisol levels were associated with primary psychopathy and higher cortisol levels were associated with secondary psychopathy, in women only. Results also showed that primary psychopathy but not secondary psychopathy was positively correlated with indirect aggression. In Chapter 4, romantic attraction was examined from an evolutionary perspective to predict the characteristics of people who invade an existing romantic relationship as well as those characteristics that predict people who are targets for defection away from their primary romantic relationship. In men, successful mate poaching was best predicted by high self-esteem, cold affect, and criminal tendencies. These men also showed lower levels of testosterone and higher levels of cortisol. In women, physical attractiveness best predicted success in mate poaching. For both sexes, physical attractiveness also determined the frequency of being a target for a poach. Collectively, these studies provide evidence to support behavioural patterns that are consistent with evolutionary ideas relating to social status acquisition and romantic attraction.
Keywords: aggression; sexual behaviour; social status; hormones; Personality and Social Contexts; Social and Behavioral Sciences; Social Psychology; Personality and Social Contexts